2022
DOI: 10.14309/ajg.0000000000002063
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Effect of Anxiety and Depression Trajectories in Inflammatory Bowel Disease

Abstract: INTRODUCTION:Symptoms of common mental disorders, such as anxiety or depression, are associated with adverse clinical outcomes in inflammatory bowel disease (IBD). We report trajectories of these symptoms in IBD, patient characteristics associated with different trajectories, and effects on healthcare utilization and prognosis.METHODS:We collected demographic, symptom, psychological, and quality-of-life data, with questionnaires at 3-month intervals, over 12 months of follow-up. We collected healthcare utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It was mentioned in the introduction that depression or other psychiatric disorders may precede the onset of inflammatory bowel disease, RA or diabetes [ 22 24 , 26 , 27 , 29 , 34 38 ]. It may also develop after the onset of all these conditions [ 20 , 22 , 24 27 , 30 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was mentioned in the introduction that depression or other psychiatric disorders may precede the onset of inflammatory bowel disease, RA or diabetes [ 22 24 , 26 , 27 , 29 , 34 38 ]. It may also develop after the onset of all these conditions [ 20 , 22 , 24 27 , 30 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was mentioned in the introduction that depression or other psychiatric disorders may precede the onset of inflammatory bowel disease, RA or diabetes [ 22 24 , 26 , 27 , 29 , 34 38 ]. It may also develop after the onset of all these conditions [ 20 , 22 , 24 27 , 30 , 39 , 40 ]. This bi-directional relationship has been shown also in the functional somatic syndromes and this has led some authors to imply that the relationship is causal in relation to IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 IBD patients often have psychological symptoms, such as depression and anxiety, which may be associated with the long disease course and daily life disorders in IBD. 4,5 A prospective cohort study based on UK biobank showed that IBD patients had a significantly higher risk of depression than non-IBD participants. 6 The prevalence of depression in UC patients is 24%, while the prevalence of depression in active UC patients is as high as 41.3%.…”
Section: Introductionmentioning
confidence: 99%